Competition Between Cα‐S and Cα‐Cβ Bond Cleavage in β‐Hydroxysulfoxides Cation Radicals Generated by Photoinduced Electron Transfer. (3rd June 2021) - Lapi, Andrea; D'Alfonso, Claudio; Del Giacco, Tiziana; Lanzalunga, Osvaldo
Abstract: A kinetic and product study of the 3‐cyano‐ N ‐methyl‐quinolinium photoinduced monoelectronic oxidation of a series of β‐hydroxysulfoxides has been carried out to investigate the competition between Cα ‐S and Cα ‐Cβ bond cleavage within the corresponding cation radicals. Laser flash photolysis experiments unequivocally established the formation of sulfoxide cation radicals showing their absorption band ( λ max ≈ 520 nm) and that of 3‐CN‐NMQ ( λ max ≈ 390 nm). Steady‐state photolysis experiments suggest that, in contrast to what previously observed for alkyl phenyl sulfoxide cation radicals that exclusively undergo Cα ‐S bond cleavage, the presence of a β‐hydroxy group makes, in some cases, the Cα ‐Cβ scission competitive. The factors governing this competition seem to depend on the relative stability of the fragments formed from the two bond scissions. Substitution of the β‐OH group with ‐OMe did not dramatically change the reactivity pattern of the cation radicals thus suggesting that the observed favorable effect of the hydroxy group on the Cα ‐Cβ bond cleavage mainly resides on its capability to stabilize the carbocation formed upon this scission. Abstract : The behavior of a series of β‐hydroxysulfoxide cation radicals, obtained by photoinduced electron transfer, have been studied via laser flash photolysis and steady state experiments with the aim to investigate the competition of Cα‐S and Cα‐Cβ bond cleavage.